Design and Construction of the Lille Langebro, Copenhagen. Issue 2 (1st September 2021) - Fryer, Simon; Eckhart, Thomas; Nugent, Peter
Abstract: The Lille Langebro is the latest movable bridge to be built across the harbour in Copenhagen. Its design was the subject of an international competition commissioned in 2014 by the client, Realdania, and won by a collaboration of Buro Happold, Wilkinson Eyre and Eadon Consulting. The bridge has an overall length of 160m and carries pedestrians and cyclists over a 7m wide deck. The superstructure is steel comprising main longitudinal members that are triangular in cross section along each edge. The geometry is complex with plan curvature and an undulating profile, resulting in an interesting form that results in double curvature of the steel plates. The bridge has two sections that swing to allow shipping through a 35m wide navigation channel. In order to maintain a slender profile in elevation, an innovative moment connection has been designed to connect the moving parts together at midspan. This connection clamps the sections together but is released to allow longitudinal movements arising from temperature. The four bridge sections were entirely prefabricated, being assembled upside down in the workshop and then turned over. They were then delivered to site by sea for erection on site using a large capacity shear leg crane.